INNOVATION OF THE MULTICULTURAL BASED BOARDING SCHOOL EDUCATION SYSTEM - Muhadjirin Muhadjirin (Universitas Islam Malang, 2022)
The innovation of the education system in Islamic boarding schools must be carried out with the aim of finding new breakthroughs in its development, so that it is hoped that there will be new findings that can give any changes in the Islamic boarding school education system. In its way, Islamic boarding school education runs dynamically in forming a multicultural community that is socio anthropologically stated as Islamic boarding school society. This is shown by the two main functions of Islamic boarding school . The first one is as an educational institution with an educational system and typical teaching learning pattern. The second one is Islamic boarding school always internalizes Islamic values in the middle of the Islamic boarding community as well as the community in general. In this case , Islamic values that are accordance with multicultural values.Multicultural education encourages educational institutions to play a role in instilling awareness in a pluralistic society and developing an attitude of tasamuh tolerance to create cooperation with all the difference that exist . Multicultural based Islamic boarding school education is a progressive approach to transform education that holistically provides critics and shows the weaknesses of failure and discrimination in the world of education. Innovation steps taken by Islamic boarding schools in respondingÃ‚Â to the dynamics of education in Indonesia, students have a formal education diploma in addition to maintain their existence as traditional educational institutions. This then makes Islamic boarding schools innovate in their policies and education systems.This research is located in two places, namely Islamic boarding school Tebuireng Jombang and Islamic boarding school Sirojul Ulum Kediri. This study aims to describe, analyze, and interpret (a) The types of innovations in the multicultural Islamic education system in the Tebuireng Islamic boarding school in Jombang and the Sirojul Ulum Islamic boarding school in Kediri. (b)The process of innovation in the multicultural Islamic education system at the Tebuireng Islamic boarding school in Jombang and the Sirojul Ulum Islamic boarding school in Kediri (c) the results of the innovation of the multicultural Islamic education system at the Tebuireng Islamic boarding school in Jombang and the sirojul ulum islamic boarding school in Kediri.The type of research used is a qualitative with a case study research approach, data collection techniques use three ways, namely observation, interview, and documentation. Then the data is analyzed by condensing the data, presenting the data, and drawing conclusions or verification. While the source of data in this study :Ã‚Â the caretaker of the boarding school, the administrator of the foundation, the head of teacher unit ,ustadz.The results of the study show that: The innovation of a multicultural Ã¢â‚¬â€œ based education system is seen in :Ã‚Â (a) the form of the salafiyah madrasah education unit (b) form of education unit madrasah diniyah (C) madrasah nidzomiyah (d) form of education unit tahfidzul quran (e) form of formal education unit consist of : (1) Islamic junior high school A and Islamic junior high school B (2) Islamic junior high school salafiyah syafiiyah (MASS) : (3) Islamic senior high school salafiyah syafiiyah (MASS) : (4) (Junior high school) and (senior high school )A Wahid Hasyim : (5) Transeins senior high school (6) Islamic Muallimin Hasyim AsyÃ¢â‚¬â„¢ari. (f) the form of a higher education unit consisting of : (1) MaÃ¢â‚¬â„¢had Aly Hasyim AsyÃ¢â‚¬â„¢ari : (2) University of Hasyim AsyÃ¢â‚¬â„¢ari .The innovation process of a multicultural based education system includes : (a) the need of the problem (b) development (c) teaching methods. The results of the innovation of a multicultural based education system are revealed in educational institutions under the auspices of Islamic boarding schools which includes : (a) tafaquh fiddin (b) mujtahid (c) proficient in Arabic (d) intellectual intelligence, social, skill, and spiritual ( e ) academic abilityÃ‚Â ( f) ahlaqul karimah (g) Muallim.The Islamic boarding school education system is actually full of multicultural life contained in it because the teachings of islam itself are very compatible with multicultural values.Ã‚Â Therefore it is necessary to explore (observe) all matters related to the boarding school education system to heal an open attitude that can adapt at any time to changeÃ‚Â times. Therefore when the religious community presents a closed interpretation of religion that is exclusively radical and even shows hostility to others, it is necessary to innovate a multicultural based education system.Keywords:Ã‚Â Innovation, Islamic Boarding School Education, Multicultural